The Eleventh Sultan Azlan Shah Lecture 1996 – Contract Law: Fulfilling The Reasonable Expectations Of Honest Men – The Right Honourable Lord Steyn - Lord Steyn, The Right Honourable (Journal of Malaysian and Comparative Law, 2019)
Text of the Eleventh Sultan Azlan Shah Law Lecture (organised by the Faculty of Law, University of Malaya and the British Council) delivered by the Rt Hon Lord Steyn, on 24 October 1996 in the presence of DYMM, Sultan Azlan Shah the Sultan of Perak.